Effects of Tai Chi Chuan training on the QoL and psychological well-being in female patients with breast cancer: a systematic review of randomized controlled trials - Li, Wenyuan; You, Fengming; Wang, Qiaoling; Shen, Yifeng; Wang, Jundong; Guo, Jing (Frontiers in Oncology, 2023)
Background: Tai Chi Chuan (TCC) may have a positive impact on physical and psychological well-beings in breast cancer patients, but the evidence remains limited and inconclusive. This systematic review aims to evaluate the effects of TCC on the QoL and psychological symptoms in women patients with breast cancer. Methods: This review has been registered on PROSPERO (ID: CRD42019141977). RCTs of TCC for breast cancer were searched from eight major English and Chinese databases. All trials included were analyzed in accordance with the Cochrane Handbook. The primary outcomes were QoL, anxiety and depression in patients with breast cancer. Fatigue, sleep quality, cognitive function and inflammatory cytokine were the secondary outcomes. Results: Fifteen RCTs involving a total of 1156 breast cancer participants were included in this review. The methodological quality of included trials was generally poor. The pooled results suggested that TCC-based exercise could significantly improve QoL (SMD=0.35, 95%CI: 0.15 to 0.55, I2=0, Model: Fixed, IV), anxiety (WMD=-4.25, 95%CI: -5.88 to -2.63, I2=0, Model: Fixed, IV) and fatigue (SMD=-0.87, 95%CI: -1.50 to -0.24, I2=80.9%, Model: Random, DL) compared other controls, with moderate to low certainty of evidence. The improvement of QoL and fatigue by TCC was also clinically meaningful. However, TCC-based exercise failed to show any between-group differences in depression, sleep quality, cognitive function and inflammatory cytokine. Post-hoc analysis revealed that TCC-based exercise outperformed the other exercise in improving shoulder function with very low certainty of evidence. Conclusion: Our findings manifested that TCC-based exercise is helpful for improving the QoL, anxiety and fatigue in patients with breast cancer within the range of comparisons covered in this study. However, the results must be treated with great caution because of the methodological flaws of included trials. Larger, well designed and conducted randomized controlled trials with longer follow-up is warranted in the future to evaluate the important outcomes of TCC for breast cancer.